Effectiveness of a case-based learning model using a digital pop-up book on students’ critical thinking skills - supardi, Niswatin Muazizah; Rahman, M. Fathur (Indonesian Journal of Educational Development (IJED), 2025)
The purpose of this study is to determine the effectiveness of the case-based learning model using digital pop-up books in enhancing students' critical thinking skills. This innovative approach aims to enhance critical thinking skills through interactive media that meet the demands of the 21st century, as outlined in the Merdeka Curriculum, which underscores the urgency of this research. The population of this study involved two classes, X6 and X8, at SMAN 1 Polanharjo, with class X6 designated as the experimental group and class X8 as the control group. The sampling technique used by the researcher was non-probability sampling of the purposive type. Critical thinking skills were measured through pretest and post-test assessments conducted before and after the learning process. The independent t-test analysis resulted in a significance value of 0.017 < 0.05, indicating a statistically significant difference. The independent samples t-test showed a meaningful difference in the average post-test scores between the experimental and control groups, leading to the rejection of Ho and acceptance of Ha. These findings emphasize that integrating digital pop-up books into case-based learning enhances critical thinking skills in real-world contexts. Therefore, the case-based learning model using digital pop-up books has proven effective in improving the critical thinking abilities of students in class X at SMAN 1 Polanharjo, offering an alternative for practical learning in an active digital era centered on students.